A Daily Life Content Analysis on the Kinderflix Youtube Channel as a Means of Imitating Early Childhood Adaptive Behavior: english - Kanisa Dewi Suci Lestari; Nurdiansyah Nurdiansyah; Gia Nikawanti (Sakura Digital Nusantara, 2026)
Purpose: In the digital era, visual media acts as a